The impact of stigma on mental health and quality of life of infertile women: A systematic review - Xie, Yue; Ren, Yue; Niu, Changmin; Zheng, Ying; Yu, Ping; Li, Lin (Frontiers in Psychology, 2023)
Introduction: Stigma affects approximately 53.08%~64% of female infertility patients worldwide. Stigma not only causes harm to the mental health of patients, but also affects their quality of life, making them bear the adverse social consequences like domestic violence, marriage breakdown, or even delay of the treatment. Therefore, it is crucial to have a deep understanding and effective intervention in patients' stigma. Aims /question: This study aims discuss and summarize the stigma in infertile women and its impact on patients, and to provide a theoretical basis for the clinical treatment and nursing intervention of disease stigma in infertile female patients. Methods: The literature search used four English databases (Cochrane Library, EMBASE, Web of Science, and PubMed) and two Chinese databases (CNKI and Wanfang). The search time of the literature is from the establishment of the library to 2022, with no language restriction. Results: The review included 30 studies, with 22 cross-sectional studies and 8 qualitative studies. This study found that social support, living environment, education level, occupation, and fertility awareness were the influencing factors of infertility stigma. Conclusions: Infertility stigma can bring heavy mental pressure and psychological burden to infertility patients and affect their quality of life. Therefore, effective and targeted psychological interventions should be developed to reduce patients' stigma and improve their quality of life. Implications for practice: Healthcare workers must develop targeted nursing interventions, provide professional counseling services to reduce the level of stigma in infertility patients, reduce fertility stress, and improve their quality of life.